In Pursuit of Water Justice in Jakarta - Tuslian, Widya Naseva; Rinwigati, Patricia; Sandyawan, Stanislaus (The Indonesian Journal of Socio-Legal Studies, 2024)
Despite becoming a rapidly growing megacity, in some of Jakarta’s areas, particularly in the underprivileged areas, a significant portion of its citizens still lack access to adequate domestic water. For years, water privatization has been considered a major barrier to solving the issue. Jakarta’s citizens have mobilized themselves to publicly reclaim Jakarta’s water governance. One of the significant actions was filing a citizen lawsuit against the relevant state authorities, which eventually was ruled in favor of the state authorities due to procedural reasons. Using the ROLAX framework developed by Bedner and Vel, this paper tries to understand to what extent the water privatization lawsuits and civil society’s legal mobilizations in Jakarta reflect an effective access to justice process. Incorporating socio-legal methods by combining empirical and doctrinal research, this paper shows that the process of access to justice is not straightforwardly related to the outcome of legal processes. In this case, the access to justice process does not end with the citizen lawsuit, as citizens’ mobilization goes beyond the courtroom. CSO’s representing citizens who experienced water access problems have adopted the courts’ favorable legal considerations in further pushing the government to conduct full public management of Jakarta’s water management and demanding the fulfilment of their water access rights.